2013
DOI: 10.1080/14697688.2012.708777
|View full text |Cite
|
Sign up to set email alerts
|

The structure of gold and silver spread returns

Abstract: The price dynamics of gold and silver have long been a matter of popular concern and fascination. The objective of this study is to investigate the dynamics of the bivariate relationship between gold and silver prices. First, we investigate the spread, measured as the price difference between gold and silver trading as a futures contract. Then the presence of a fractal structure is measured using statistical techniques based on rescaled range analysis after accommodating short-term autocorrelated innovations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 44 publications
(42 reference statements)
0
16
0
Order By: Relevance
“…Recent studies found indications of time-varying long memory in financial time series (Cajueiro and Tabak 2004;Carbone, Castelli, and Stanley 2004;Hull and McGroarty 2014;Auer 2016b). Batten et al (2013) and Auer (2016a) explored possible applications for the development of profitable trading strategies. They used estimates of the Hurst coefficient H, which is related to the memory parameter d via H ¼ d þ 0:5, for the generation of buy and sell signals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies found indications of time-varying long memory in financial time series (Cajueiro and Tabak 2004;Carbone, Castelli, and Stanley 2004;Hull and McGroarty 2014;Auer 2016b). Batten et al (2013) and Auer (2016a) explored possible applications for the development of profitable trading strategies. They used estimates of the Hurst coefficient H, which is related to the memory parameter d via H ¼ d þ 0:5, for the generation of buy and sell signals.…”
Section: Resultsmentioning
confidence: 99%
“…They used estimates of the Hurst coefficient H, which is related to the memory parameter d via H ¼ d þ 0:5, for the generation of buy and sell signals. Batten et al (2013) used the values -0.1 and 0.1 as thresholds (for estimates of d, i.e., 0.4 and 0.6 for estimates of H) and a rolling window of 22 trading days. In an effort to reduce transactions costs by reducing the trading frequency, Auer (2016a) increased the threshold values to -0.2 and 0.2 and the window size to 240 trading days.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Baur and Tran () concluded that there is a close relationship between gold and silver returns in the long term, which is affected significantly during distress periods. Finally, Narayan, Narayan, and Sharma () and Batten, Ciner, Lucey, and Szilagyi () underline the importance of using commodities within profitable trading strategies, though the performance of these strategies could be affected significantly during distressed periods, as was the case within the recent financial crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Studying emerging stock markets, Cajueiro and Tabak [21], Hull and McGroarty [65] and Auer [27] observed time-varying estimates of the Hurst exponent H. Batten et al [25] and Auer [28] took things a step further. Assuming that fractal dynamics does in fact exist in precious metal returns, they explored possible trading strategies that are based on local estimates of H. In contrast, Reschenhofer et al [66] found no evidence of long-range dependence, neither in stock index returns nor in gold returns.…”
Section: Resultsmentioning
confidence: 99%